Laporan Kasus: Otitis Externae Sirkumkripta - Bauzir, Amanda Muhamad; Siahaan, Ruth Mindo; Fadhyki, Arsiyoga Bimo; Haniifah, Ulaa; Anas, Muhammad (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Circumcrypt otitis externa (OE) is an inflammation accompanied by furuncle growth in the outer ear with or without infection. Circumcrypt OE events are identified with swimmers or other names Swimmer's Ear because their ears are moist. Circumcrypt OE cases can be distinguished based on the duration of action, acute or chronic. Case Report: A 21-year-old male patient complained of ear pain; previously, the patient also felt a feeling of fullness in the ear. Previously the patient had a history of swimming and cleaning the ears afterward. Another complaint is decreased hearing and yellow discharge from the left ear. Conclusion: Circumscribed otitis externa or Swimmer's Ear is an ear inflammation caused by bacteria, fungi, or their groups that grow in moist places. To make a diagnosis through anamnesis, examination of local status, and support. OE management can be done with pharmacology and spooling measures to clean the ears